2017
DOI: 10.1016/j.econmod.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of equity ownership groups on investment: Evidence from Ukraine

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. We would like to thank the Editor and two anonymous referees for their very valuable comments that improved the paper significantly. We are also grateful to Anton Andrianov and to Dragon Capital for permission to use their data. Permanent repository link

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…on the monitoring role of managerial ownership. This means that managerial shareholders are essential for enhancing corporate investments (Mykhayliv & Zauner, 2017), and for offsetting market inefficiency (Nakabayashi, 2019). The finding of this study is in tandem with Bilal et al (2018) and Bryce et al (2015) who showed the link between the audit committee and EQ with the IFRS adoption.…”
Section: The Moderating Effect Of Ifrs Adoptionsupporting
confidence: 69%
See 1 more Smart Citation
“…on the monitoring role of managerial ownership. This means that managerial shareholders are essential for enhancing corporate investments (Mykhayliv & Zauner, 2017), and for offsetting market inefficiency (Nakabayashi, 2019). The finding of this study is in tandem with Bilal et al (2018) and Bryce et al (2015) who showed the link between the audit committee and EQ with the IFRS adoption.…”
Section: The Moderating Effect Of Ifrs Adoptionsupporting
confidence: 69%
“…Third, auditors can significantly reduce the risk levels of earnings management when there is a high percentage of managerial ownership (Alzoubi, 2016). It was also noted by Tran (2014) that managerial ownership was negatively associated with the cost of financing, but it enhanced corporate investments (Mykhayliv & Zauner, 2017), and it encouraged companies to have long-term growth (Nakabayashi, 2019). It appears that when directors were also shareholders, markets tend to react more favourably (Qian, Sun, & Yu, 2018).…”
Section: Managerial Ownership Ifrs Adoption and Eqmentioning
confidence: 99%
“…In figure 3.21, countries rated 100 such as USA, Luxembourg, Netherlands and Australia are considered riskless, Prime or high-grade rating AAA+ (Trading Economics, 2019). Countries such as Ukraine, Zambia, DRC and Puerto Rico are countries that have extreme high risk, and not recommended for investment (Mykhayliv & Zauner, 2017). South Africa has a credit rating of BB, which is below investment zone, meaning that it has investment uncertainties (Trading Economics, 2019).…”
Section: Why Are South Africans Paying So Much Tax?mentioning
confidence: 99%
“…In addition, the existing corporate governance studies still have shortcomings as in the study of Connelly et al, (2017), who studied the relationship between weak corporate governance and unobserved investment decisions. Moreover, there is still inconsistency in terms of influence of share ownership on investment decisions as Mykhayliv and Zauner (2017) state that insider shareholdings and industrial and financial groups do not influence investment. It is, therefore, necessary to further study the influence of corporate governance on more specific investment decisions.…”
Section: Bibliometric Network Analysismentioning
confidence: 99%
“…According to Mykhayliv and Zauner (2017), the majority of shareholders and the increase in state share ownership have a negative influence on the company investment, such as domestic share ownership and financial institutions whereas the insider shareholdings and industry and financial groups do not affect investment.…”
Section: Bibliometric Network Analysismentioning
confidence: 99%